Genetic diversity of genotype 6 HCV infections in France: Epidemiology and consequences for treatment strategy. Issue 11 (29th July 2019) - Pronier, Charlotte; Fontaine, Hélène; Dorival, Céline; Carrat, Fabrice; Pol, Stanislas; Thibault, Vincent; ,
Abstract: Genotype‐6 hepatitis C virus (GT6‐HCV) exhibits a high genetic diversity. GT6 prevalence, diversity and real‐life response to treatment were studied among 14 603 HCV mono‐infected patients from the French ANRS‐CO22‐Hepather cohort. NS3, NS5A and NS5B‐HCV genes were amplified and sequenced for all GT6‐infections identified in the database. Following phylogenic characterization, resistance‐associated substitution polymorphisms were identified. GT6‐infected patients (n = 36; 0.25%) did not differ from patients infected with other genotypes with regard to gender, age or liver fibrosis. GT6e was the most prevalent (27.8%), followed by 6a (22.2%), 6q (11.1%) and 6o (8.3%). Each subtype p and xc were found in two patients (5.6%) and subtypes f/h/r and t were each detected in one patient. Four strains (11.1%) clustered with unclassified reference sequences. Concordant genotype determination throughout NS3, NS5A and NS5B‐genes is consistent with lack of recombination within this genomic region. All, but three patients were born in Asia, Cambodia (44.4%), Vietnam (38.9%) or Laos (8.3%). GT6a were found in 42.8% of Vietnamese and 6e in 37.5% of Cambodian. GT6q, 6p and 6r were only found in Cambodian patients. Resistance‐associated polymorphisms for each DAA classes were identified in baseline sequences. Twenty‐seven patients were treated with sofosbuvir‐based combinations and 3 with glecaprevir/pibrentasvir. All treated patients, whether naïve or previously treated, achieved a sustained viral response. In conclusion, GT6‐infections are uncommon in France and their genetic diversity likely reflects infection within the country of origin. Despite residue variability at DAA resistance‐associated positions, sustained viral response was obtained in all treated patients.